Evaluation Report on Oilseeds Development Programme - Planning Commission (Planning Commission, 1981)
Oilseeds production occupies an important place in India’s agricultural economy. These crops also constitute a spring board for numerous agrobased industries such as oil pressing and refining, vanaspali, manufacture of soaps, paints, varnishes and a number of other products. State Governments have been implementing under the State sector, several schemes for increasing the production of oilseeds crops.
Programme Evaluation Organisation, Planning Commission, Government of India